Analisis Pengaruh Partisipasi Anggaran Dan Informasi Asimetri Terhadap Senjangan Anggaran (Budgetary Slack) Pada Perguruan Tinggi Swasta Di Kabupaten Pamekasan - Oktaviana Dewi, Ika (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
Abstract: Someone's involvement in budgeting will create a budgetary slack. This article aims to analyze the effect of budgetary participation and information asymmetry on budgetary slack. This type of research includes quantitative research, the focus of which will be directed at budgetary participation and information asymmetry in private universities in Pamekasan. Furthermore, the data were analyzed using statistical tests such as data quality tests, classical assumption tests and hypothesis testing. The results showed that the first hypothesis was accepted, which means that there was a significant influence between budgetary participation and budgetary slack. For the second hypothesis it is also accepted that there is a significant influence between information asymmetry on budgetary slack. The third hypothesis is tested simultaneously, the results are budgetary participation and information asymmetry together can create a larger budgetary slack.